Effect of Weed Management Practices on The Growth and Yield of Cassava ( Manihot esculenta Crantz) - Velmurugan, M; Manickam, S.; Pugalendhi, L (JOURNAL OF ROOT CROPS, 2017)
Field experiments on the effect of weed management practices on the growth, tuber yield and weed control efficiency in cassava were conducted at Tapioca and Castor Research Station, Yethapur under AICRP Tuber crops programme during the period 2010 . 2014 with an objective of identifying the suitable weed management strategies to improve growth, tuber yield and starch content of cassava. The cassava setts of var. CO (Tp) 4 were planted on ridges at a spacing of 90 x 75 cm. The experiment was planned with ten treatments in Randomized Block Design (RBD) with three replications with the combinations of hand weeding, herbicide application and its combinations which were compared with absolute control (unweeded plots). The growth parameters viz., plant height and stem girth, yield parameters viz., mean number of tubers plant -1 , tuber yield, starch content and weed parameters viz., weed density and weed control efficiency and benefit cost ratio were recorded. Among the different weed management practices adopted, the maximum tuber yield (38.40 t ha -1 ) was recorded in treatment with black polythene mulching. Different weed control measures do not influence the starch content of tubers. Invariably at all stages of the crop growth, polythene mulched plots were free from weeds and recorded 100 % weed control efficiency. The maximum B:C ratio was also obtained in black polythene mulching (4.2) when compared to other weed management practices. However, the lowest B:C ratio (1.9) was recorded in the unweeded check.